Effect of Aspergillus spp., magnetized water and Granstar in control of wild radish weed (Raphanus raphanistrum L.) and growth of wheat plant( Triticum aestivum L.) in one of the fields Al-Hirah in Najaf province - AL-Shebly, Hayder A. A.; Alwan, Sabah L. (Journal of Kerbala for Agricultural Sciences, 2017)
magnetized water(MW), the fungus Aspergillus spp. the herbicide Granestar on wheat growth. In a preliminary experiment, magnetized water at three magnetic density levels (1600, 3200, 4800) Gauss was tested to determine the better intensity for seed germination and plant growth of wheat and the wild radish weed. The aim of the study was to control the wild radish in the wheat fields by developing an integrated program to reduce the use of chemical pesticides by using environmentally friendly agents including the bio-agent fungus Aspergillus spp., magnetized water as a physical agent and the Granstar herbicide. solani and Aspergillus spp. were isolated from wheat and wild radish seedlings and pathogenically tested on both host plants. Results showed that both R. solani and Aspergillus sp. increased germination and seedlings growth of the wheat and inhibited germination and growth of the wild radish. Aspergillus spp. had no negative effects on seed germination and seedlings growth where tested on different plant families seeds including cow pea, cucumber, radish, barley, melon, garden cress and green mung beans. Seed germination percentage and seedlings length of wheat and wild radish were affected by magnetic intensity levels after 21 days of planting. The 1600 G was the best treatment for seed germination and seedlings length of wheat, and at the same time this intensity level negatively affected the wild radish seeds and seedlings resulted in the lowest values of germination and seedlings length. However, the highest intensity level 4800 G did support highest seed germination percentage and seedlings length of the wild radish, but this intensity had negative effects on wheat seeds germination and seedlings length. The main field experiment was conducted during the winter growing season of 2016 in one of Al-Hirah wheat field in the province of Najaf. The experiment was factorial with two factors, MW as main factor and the fungus Aspergillus spp. and the herbicide Granstar at half and full of recommended dose based on RCBD design with three replicates. The treatment of MW (1600 G) significantly increased all plant growth parameters tested (Weight of spike, weight of 1000 seeds, and total yield) compared to the control (RW). All treatments combinations that included the bio-agent Aspergillus spp. Resulted in enhancing all growth and yield parameters tested with total yield of 5.505 ton.h-1 compared to 2.778 ton.h-1 from the plants not treated with the fungus.